(3GddjK GdYGHS aj UOeGJ GdeLGdSs - (3ESeGYjd Hf Ydj Hf MSf GdUYjOj GdbGgQj GdTGaYj, GHf eYdjs
(3ChdgG (B:s
(3GdMeO ddg GdPi gh CUd ddYGde ai GdEjLGO, GdYGde HCSQGQge hGdNGdb dCaYGd GdYHGO, CMeOg MeOG jOhe HOhGeg, hCTcQg Ydi eG GhdGfG ef LRjd EfYGeg s
(3BNQgG (B:s
(3hZRhGJg Udi Gddg Ydjg hSde NeSI hYTQhf ZRhI, hbjd(B: (3SHY hYTQhf, hSQGjGg SJI hNeShf, hbjd(B: (3ZjQ Pdc, hGddg CYde s
(3Vef eLehY , JQJjHgG (B: 1s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B370s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1571s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3MGdI GdfSNI LjOI s
Keywords: (3CUhd Gdabgs